The Misconceptions (Jadal) in Quran - Muhammad Kamal-Deen Bello; Abdoul Karim Toure; Adnan Mohamed Yusoff (USIM PRESS, 2024)
Jadal (argumentation) is a method of expression that the Qur’ān Karim, the holy book of the Muslims embarks on in preaching its missions and conveying its messages. It also serves as guidance in everything, be it religious or otherwise. It takes some measures and methods to deliver and convey its messages to the word, e.g. qissah (story), qasam (oath), hathal (proverbs), hiwār (communication), Jadal/Muhājjah (argumentation) inclusive. However, out of these Qur’ānic methods, only argumentation (jadal/muhājjah) remains controversial that some scholars and writers have bias mind with. Some talk about its prohibition in the two major sources of sharī'ah, Qur’ān and Sunnah. Some suggest abrogation of its verses in the Qur’ān, while other sees it as unlawful thing that should not be approached or drawn near to at all by a Muslim. It is against this background that this paper wants to examine study further and assess critically the misconceptions surrounding this natural phenomenon (jadal) in the light of the holy book; Qur’ān.